Studi Eksplorasi Konsep Etnosains Masyarakat Ambarawa dan Kaitannya dengan Pembelajaran Ilmu Pengetahuan Alam di Sekolah Dasar - Anny Fitria Devi; Anatri Desstya (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The purpose of this research is to (a) analyze the IPA concept in brick making, and (b) explore the IPA concept in swamp fishing. This study uses a qualitative approach with a phenomenological design. Asinan Village in Semarang Regency, Central Java, became the research location. Primary data sources involved were brick manufacturers and RT heads, while secondary data sources were documents related to the topics discussed. Methods of data collection is done through interviews, observation, and written notes. Data analysis techniques, including filtering, visualization, and inference. Triangulation of data sources is used to check the validity of the data and ensure the authenticity of the data. The findings show that a). In the process of making bricks, there is a molding process which contains the basic concepts of IPA: force, in the process of drying the bricks contain the basic concepts of IPA heat transfer, in the process of burning bricks contains the IPA concepts of physical changes and chemical changes. b). In fishing activities in the swamp, there is an activity of throwing bait which contains the concept of various styles.